(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The implementation of a Quality Management System (QMS) is a crucial step for enterprises aspiring to enhance their operational efficiency and product/service quality. Certification stages play a pivotal role in validating the effectiveness of a QMS, ensuring adherence to international standards, and demonstrating a commitment to continuous improvement. This abstract explores the significance of certification stages in enterprises with a QMS, highlighting their impact on organizational processes, customer satisfaction, and market competitiveness.